Professional Exhaustion in Teachers of higher Education: The case of USMBA teachers - BELKHOU , Asmae; GHALMAT , Mounia (Revue Internationale des Sciences de Gestion, 2022)
A widespread phenomenon or the disease of the century, stress or commonly called “fatigue” is an increasingly popular issue. We all experience times of stress or hyperactivity, more or less intense, forcing us to tap into our energy reserves which are far from being inexhaustible. Stress is, therefore, recognized as a significant problem among teachers. In fact, the various tasks and responsibilities assigned to them regularly, the complex development of the educational system, and the health crisis linked to COVID 19, put them in situations demanding permanent efforts that undoubtedly generate stress. All these parameters are the basis of our research. Studying professional burnout among higher education teachers at Sidi Mohammed Ben Abdellah University is timely and important. The survey is meant to investigate the real mind of teachers at Moroccan University. The choice of the Likert scale is justified by our concern to bring our statistical results showing their level of stress. 60 university professors of different disciplines and different higher education institutions responded to the survey.